1984
DOI: 10.1029/jb089ib07p05817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical fault properties on frictional instabilities produced on simulated faults

Abstract: Laboratory studies of large-scale simulated faults show that physical properties of the fault, specifically normal stress and fault roughness, significantly influence the unstable shear failure behavior of the fault. In addition, the experiments provide insights into important length-scaling effects that are useful for assessing concepts such as critical crack length or rupture nucleation dimension. Stick-slip shear failures have been generated along a 2-m-long simulated fault in a block of Sierra white granit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
228
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(260 citation statements)
references
References 30 publications
(48 reference statements)
30
228
2
Order By: Relevance
“…Previous work on meter-sized laboratory samples at 5 MPa normal stress indicated that the critical nucleation size R C~1 m [Okubo and Dieterich, 1984;Beeler et al, 2012;McLaskey and Kilgore, 2013]. The current experiments were conducted at about 20 times higher stress levels (~100 MPa) so we estimate that R C is about 20 times smaller.…”
Section: Estimates Of R Cmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous work on meter-sized laboratory samples at 5 MPa normal stress indicated that the critical nucleation size R C~1 m [Okubo and Dieterich, 1984;Beeler et al, 2012;McLaskey and Kilgore, 2013]. The current experiments were conducted at about 20 times higher stress levels (~100 MPa) so we estimate that R C is about 20 times smaller.…”
Section: Estimates Of R Cmentioning
confidence: 80%
“…The current experiments were conducted at about 20 times higher stress levels (~100 MPa) so we estimate that R C is about 20 times smaller. This is approximate since nucleation size is also known to be a function of fault roughness [Okubo and Dieterich, 1984] and loading history [Fang et al, 2010;Kaneko and Lapusta, 2008].…”
Section: Estimates Of R Cmentioning
confidence: 99%
“…Acoustic sensors have been widely applied to study analogue earthquakes: Johnson et al (1973), Wu et al (1972), and Okubo and Dieterich (1984) used piezoelectric transducers to estimate slip rate and rupture speed in stick-slip experiments on precut rock and rock analogue materials. Lockner et al (1991), Zang et al (2000), and Thompson et al (2005, (2008) and Zigone et al (2011) used acoustic emission to characterize the stick-slip process in a spring-slider and salt-slider set-up (Fig.…”
Section: Local Monitoring Techniquesmentioning
confidence: 99%
“…It was studied experimentally using fault block models using precut rock (e.g. Dieterich, 1978a;Okubo and Dieterich, 1984;Ohnaka and Shen, 1999;McLaskey and Kilgore, 2013;McLaskey and Glaser, 2011;McLaskey et al, 2012) as well as rock analogues, e.g. polycarbonate (e.g.…”
Section: Rupture Dynamicsmentioning
confidence: 99%
“…Large overshoot has been suggested in the case the Cajon Pass borehole earthquakes (Beeler et al, 2003). Evidence from laboratory stick-slip friction experiments (Lockner and Okubo, 1983;Okubo and Dieterich, 1984) and observations from mining-induced events (McGarr, 1994) also indicate small or moderate overshoot.…”
Section: A5 Validitymentioning
confidence: 94%